Equação do primeiro grau em livros didáticos sob a ótica da teoria antropológica do didático - Barbosa, Edelweis José Tavares (2011)
The aim of this research study was to analyzing the possible changes on the introduction of the first degree equation concept in Brazilian second level textbooks, having them approved by the Textbook National Program (PNLD). In this sense, the Didactical Anthropological Theory (TAD), proposed by Chevallard and colleagues, based our research study theoretically speaking. This approach considers the mathematical objects not existent in them, but as entities which emerge from systems of practices that exist in certain institutions. We treat specifically of characterizing the Mathematical Organizations and the Didactical Organizations related to the concept of first degree equation, by focusing in two collections of the year 7 of second level approved in the 1999, 2002, 2005, 2008 and 2011 evaluations. The research results pointed out that the existent organizations in these collections were not always done in a way of clarifying the existent differences between the worked subtypes of tasks, as well as the potentialities of organized or systematized techniques. We verified that the collections did not modify the mathematical praxeologies along the evaluations. However, we noticed that the authors modified their collections in relation to the didactical praxeologies.